Effect of Alcohol Extract of Cucurbita maxima (Pumpkin) Seeds on Alanine Aminotransferase (ALT) Levels in Streptozotocin Induced Diabetic Male Long Evans Rats (Community Based Medical Journal, 2026)
An experimental study was done in the Department of Pharmacology & Therapeutics, Dhaka Medical College, Bangladesh, between January and December of 2023, to evaluate the hepatoprotective effect of alcohol extract of Cucurbita maxima (pumpkin) seeds on alanine aminotransferase (ALT) in streptozotocin induced diabetic male long Evans rats. A total of 25 rats were divided into 5 groups (i.e., 5 rats in each group): group A (non-diabetic control), group B (untreated diabetic control as diabetes induced by streptozotocin 50mg/kg body weight given intraperitonially), group C (low dose experimental group treated with pumpkin seeds 100mg/kg body weight orally), group D (high dose experimental group treated with pumpkin seeds 200mg/kg body weight orally), and group E (treated with metformin 100 mg/kg body weight orally along with laboratory diet). Group A had normal fasting blood glucose and serum ALT level, while group B had hyperglycemia with significant increase in ALT level (p